Pregnancy outcomes in the in vitro fertilization conceived polycystic ovary syndrome patients: a prospective study - Golandaz, Ruksar; Mishra, Sneha; Gupta, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: In vitro fertilization (IVF) is the need of modern era which was first developed to overcome the infertility resulting from irreparable tubal disease but now is applied more broadly for treatment of all causes of infertility including polycystic ovary syndrome (PCOS) and is associated with obstetric complications as well. This study aimed to whether pregnancy-related outcomes and complications are differed between patients with polycystic ovary syndrome (PCOS) and those with other causes of infertility who had undergone IVF. Objective were to compare maternal and fetal outcome in IVF conceived women with PCOS v/s without PCOS. Prospective comparative study at a tertiary care hospital. Methods: After getting approval from institutional ethical and scientific research committee, 108 IVF conceived women are studied, where IVF is done using controlled ovarian stimulation with GnRH antagonist protocol followed by freeze all strategy and preparation of endometrial lining. Frozen embryo transfer done in subsequent cycle over a period of one year. Study group includes women with PCOS and control group includes women without PCOS. The entire data is statistically analysed using statistical package for social sciences (SPSS ver 22.0, IBM Corporation, USA) for MS Windows. Results: Out of 108 IVF conceived pregnant women studied, 50% were PCOS (study group) and 50% non PCOS (control group). We have compared maternal and neonatal outcome in both the groups which shows patient in PCOS group has higher incidence of GDM, severe pre-eclampsia, preterm labour, LBW babies, SGA babies and babies admitted to NICU. Conclusions: Women with PCOS should be given notice of additional adverse pregnancy outcomes as well receiving early diagnosis and treatment for these complications during pregnancy and postpartum period.